Ranking of the best undergraduate programs in Administration in Colombia based on the research criteria from period 2016-2017 (2018)
This document presents a proposal to classify the Colombian administration faculties with undergraduate programs based on indicators of knowledge generation. This study was developed under quantitative parameters in which a process of comparative and interpretative analysis of the information contained in specialized academic rankings of the year 2017 was carried out, as well as of the data obtained from the research groups and postgraduate programs of the best universities that are consigned in their websites and in the GrupLac platform of Colciencias. The final classification contains nineteen programs and provides an overview of the status of some of the best undergraduate programs in Administration in Colombia. It is concluded that it is necessary to improve the ratio of postgraduate programs versus quality and quantity of research groups, which would allow the Faculty of Administration with the worst positions to improve their quality indicators of their undergraduate programs.